2013
DOI: 10.1007/s00586-013-2953-8
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal changes in cervical spine alignment after corrective thoracolumbar deformity surgery

Abstract: In spinal deformity procedures, preoperative spinal alignment parameters, and surgical plans could affect postoperative cervical spine alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 22 publications
(33 reference statements)
2
77
1
Order By: Relevance
“…49 Ha and colleagues subsequently confirmed this observation and further identified key radiographic parameters associated with these compensatory changes. 17 In addition, a high prevalence of concomitant CSD has been reported among adults with thoracolumbar deformity. 46 Collectively, these and other studies emphasize that assessment and classification of CSD should not occur in isolation and that alignment of the thoracolumbar spine and pelvis should also be assessed.…”
Section: Srs-schwab Classification Modifiermentioning
confidence: 99%
“…49 Ha and colleagues subsequently confirmed this observation and further identified key radiographic parameters associated with these compensatory changes. 17 In addition, a high prevalence of concomitant CSD has been reported among adults with thoracolumbar deformity. 46 Collectively, these and other studies emphasize that assessment and classification of CSD should not occur in isolation and that alignment of the thoracolumbar spine and pelvis should also be assessed.…”
Section: Srs-schwab Classification Modifiermentioning
confidence: 99%
“…Similarly, Lafage et al 18 reported a spontaneous increase in unfused TK following lumbar 3-column osteotomies. Lastly, both Smith et al 26 and Ha et al 14 reported spontaneous improvement of cervical alignment after correction of global sagittal malalignment following lumbar pedicle subtraction osteotomy. These studies focus on thoracolumbar deformities.…”
mentioning
confidence: 99%
“…1,14,16,26 The majority of literature regarding the management of ASD has focused on the thoracolumbar region with little regard for the adjacent regions. Several recent studies have demonstrated that regional spinal alignment and pathology can affect other spinal regions.…”
mentioning
confidence: 99%
“…Nine patients (18 %) were fused from the higher lumbar spine to the lower lumbar spine (4) or the sacrum (5), 26 (52 %) were fused from the lower thoracic to the lower lumbar spine (7) or the sacrum (19) and 15 patients (30 %) were fused from the higher thoracic to the lower lumbar spine (2) or the sacrum (13). The lower instrumented vertebra was L4 in 5 patients, L5 in 9 patients, and S1 in the remaining 41.…”
Section: Resultsmentioning
confidence: 99%